1998
DOI: 10.1021/ja972291q
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli β-Galactosidase Recognizes a High-Energy Conformation of C-Lactose, a Nonhydrolizable Substrate Analogue. NMR and Modeling Studies of the Molecular Complex

Abstract: The enzyme-bound conformation of C-lactose, an Escherichia coli β-galactosidase inhibitor has been determined by NMR spectroscopy. It is demonstrated that the enzyme selects a high-energy conformation of this closely related structural analogue of the natural substrate, lactose. In addition, a molecular modeling protocol has been performed in order to obtain a detailed three-dimensional structure of the complex that can explain, in structural terms, the role that the key amino acid residues play in the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 47 publications
8
106
1
Order By: Relevance
“…Alternatively, the conformational itinerary of ␤-galactosidases (or phosphorylases acting on ␤-galactosyl bonds) may be different from those of ␤-glucosidases because of potential crashes between the axial C4 hydroxyl and ␤-anomeric substituents. Espinosa et al (59) conducted an NMR study of a nonhydrolyzable C-glycoside analogue of lactose bound to E. coli GH2 ␤-galactosidase. They suggested that the galactopyranose ring of the bound analog is not in a distorted conformation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the conformational itinerary of ␤-galactosidases (or phosphorylases acting on ␤-galactosyl bonds) may be different from those of ␤-glucosidases because of potential crashes between the axial C4 hydroxyl and ␤-anomeric substituents. Espinosa et al (59) conducted an NMR study of a nonhydrolyzable C-glycoside analogue of lactose bound to E. coli GH2 ␤-galactosidase. They suggested that the galactopyranose ring of the bound analog is not in a distorted conformation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the way the enzyme binds to lactose [13]. According to [13] lactose can be positioned on the enzyme via several hydrophobic contacts and intermolecular hydrogen bonds (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These spectra were acquired with the proton offset at about 4.6 ppm and a sweepwidth of about 6 ppm. In the 13 C dimension the offset was placed around 80 ppm and a sweep width of 60 ppm was used. Typically, 300-350 free induction decays of 1024 data points were acquired using 128-256 scans per decay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations